Organizational factors that contribute to police misconduct among Royal Malaysian Police Force (RMPF) in Kuala Lumpur and Selangor Malaysia - Teh, Ming Tat (2024)
Police misconduct is a significant issue worldwide, affecting public trust and societal order. This study examines the organizational factors contributing to police misconduct, focusing on police officers in Kuala Lumpur and Selangor. Findings from police-related research align with general occupational and management studies, suggesting that police officers may react similarly to other employees when facing organizational mistreatment. The study aims to identify specific organizational factors influencing police misconduct. A sample of 379 police officers from Kuala Lumpur and Selangor were randomly selected, as these two regions reported the highest cases of misconduct. Data were collected using a questionnaire based on a Likert scale, and the results were analyzed through the Statistical Package for the Social Sciences (SPSS) to determine relationships between the variables. The study focused on the role of leadership, organizational culture, and work environment, as well as organizational structure and training and development. The findings revealed that leadership, organizational culture, and work environment significantly influence police misconduct. However, factors such as organizational structure and training and development did not have a noticeable effect. These results suggest that leadership practices, cultural norms within the organization, and the overall work environment play a key role in shaping police officers' behaviours. This research provides valuable insights for the top management of the Police Service, particularly in Kuala Lumpur and Selangor, to understand the current situation and how organizational factors affect police misconduct. The study highlights the need for police headquarters to address these factors to improve officers' performance and reduce incidents of misconduct. Future research could extend to other states or regions, considering additional organizational variables that reflect current needs. The implications of this study emphasize the importance of improving leadership, organizational culture, and the work environment to foster ethical behaviour and accountability within police departments.